HUBUNGAN USIA, JENIS KELAMIN, DAN TINGKAT KEPOSITIFAN DENGAN KONVERSI BASIL TAHAN ASAM PASIEN TUBERKULOSIS DI UNIT PENGOBATAN PENYAKIT PARU-PARU PONTIANAK PERIODE 2009-2012 - ., Fransiska Anggraeni Utami (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: Conversion of Acid Fast Bacilli (AFB) can predict treatmentoutcome of tuberculosis patient. AFB conversion affected by many factorssuch as age, gender, and sputum grading. The aims of this study is find therelationship between age, gender, sputum grading with AFB conversion intuberculosis patients in UP4 Pontianak. Metodology: This research wasanalytic study with cross sectional design that conducted in UP4 Pontianakwith 73 samples taken from medical record and analysed by Chi-Square test.Result: There was not significant relationship between age (p = 0,362) andgender (p = 0,366) with AFB conversion. There was a significant relationshipbetween sputum grading (p = 0,01) with AFB conversion. Conclusion:sputum grading influence AFB conversion.Keyword: Age, gender, sputum grading, Acid fast bacilli conversion, lungtuberculosis